EFFERVESCENT TABLET FORMULATION OF TURMERIC EXTRACT (CURCUMA DOMESTICA) WITH ARTOCARPUS HETEROPHYLLUS SEED STRACH AS A BINDER AND SIRAITIA GROSVENORII AS A SWEETENER - MAULANA, MOCHAMAD LUQNI; ALFIAN, MUHAMMAD; FAIZAH, NURUL (International Journal of Applied Pharmaceutics, 2025)
Objective: The appropriate processing of natural ingredients, such as turmeric, into forms that are well-received by the public is anticipated to enhance practicality and public interest. One approach involves incorporating natural ingredients, like Artocarpus heterophyllus seed starch as a binder and Siraitia grosvenorii as a sweetener, into turmeric extract effervescent tablets. Methods: Turmeric extract is formulated into three different groups: K(-) negative group without binders and sweeteners, K(+) positive group with PVP and aspartame, F1 (Formula 1), F2 (Formula 2), and F3 (Formula 3) with varying proportions of jackfruit seed starch and lo han kuo granules (3:15%, 5:25%, and 7:35%). Effervescent tablets are produced using the wet granulation method. Each formulation undergoes physical evaluation tests for the granules, including for moisture, flow time, angle of repose, and compressibility. Following this, the physical properties of the effervescent tablets are evaluated for weight uniformity, size uniformity, hardness, friability, dissolution time, pH, dissolution, curcumin content, and hedonic aspects with the use of statistical tests. Results: The turmeric extract contained 76.44% curcumin. Different concentration of Artocarpus heterophyllus seed starch had a significant impact (p<0.05) on enhancing various characteristics of effervescent granules, including the angle of repose, compressibility, weight uniformity, hardness, and dissolution time of effervescent tablets. However, these variations did not significantly affect (p>0.05) the moisture test, effervescent granule flow time, uniformity of size, pH, dissolution, and curcumin content in effervescent tablets. Conclusion: F3 is the ideal formula for testing the physical properties of granules and effervescent tablets. It is the most preferred due to its color, aroma, and taste.